GREEN ENTREPRENEURSHIP IN SMES: DRIVERS, BARRIERS, AND IMPACT ON SUSTAINABLE INNOVATION - Abdullayeva Dilnoza Bahodir qizi (Innovate Conferences, 2025)
The growing urgency of environmental challenges has positioned green entrepreneurship as a vital approach for achieving sustainable innovation, particularly among small and medium-sized enterprises (SMEs). By integrating eco-innovation into business models, SMEs can enhance their competitiveness while contributing to environmental and social well-being. However, the transition toward sustainable practices is shaped by various drivers, such as market demand, regulatory requirements, and environmental awareness, as well as barriers, including financial constraints, limited expertise, and technological gaps. Understanding these factors is essential for fostering eco-innovative strategies that not only address sustainability goals but also secure long-term competitive advantage in increasingly dynamic markets.
Keywords: green entrepreneurship, sustainable innovation, SMEs, competitiveness, drivers, barriers, eco-innovation.